Methods report on the development of the 2013 revision and update of the EAACI/GA2LEN/EDF/WAO guideline for the definition, classification, diagnosis, and management of urticaria. Issue 7 (July 2014) - Zuberbier, T.; Aberer, W.; Asero, R.; Bindslev‐Jensen, C.; Brzoza, Z.; Canonica, G. W.; Church, M. K.; Ensina, L. F.; Giménez‐Arnau, A.; Godse, K.; Gonçalo, M.; Grattan, C.; et al.
Abstract This methods report describes the process of guideline development in detail. It is the result of a systematic literature review using the 'Grading of Recommendations Assessment, Development and Evaluation' (GRADE) methodology and a structured consensus conference held on 28 and 29 November 2012, in Berlin. It is a joint initiative of the Dermatology Section of the European Academy of Allergy and Clinical Immunology (EAACI), the EU‐funded network of excellence, the Global Allergy and Asthma European Network (GA2LEN), the European Dermatology Forum (EDF), and the World Allergy Organization (WAO) with the participation of delegates of 21 national and international societies. This guideline covers the definition and classification of urticaria, taking into account the recent progress in identifying its causes, eliciting factors and pathomechanisms. In addition, it outlines evidence‐based diagnostic and therapeutic approaches for the different subtypes of urticaria. This guideline was acknowledged and accepted by the European Union of Medical Specialists (UEMS) and is published in Allergy 2014; 69:868–887.